(untitled) (PANGEEA, 2025)
The optimization of geographical space in the Lupşa common. Located in the central and western parts of the country, common Lupsa will be carried out on the middle of Aries, one of the main thoroughfares of hydrographic Apuseni Mountains. Absence of Lupsa of some industrial activities itself, pollutants, decreases to a certain extent this danger, but sources and types of pollution being varied, it may be appropriate and methods of varied combat. The people are brought profound changes potential green by creating a human heightened as a result of holdings of raw materials (construction materials, gold etc). It can be said that his current period shall include the most spectacular changes of anthropogenic environment geographically, what have they create from many places landscapes with everything distinguished from the true-to-life.